Chapter Ritirata sostenibile! I tanti modi con cui possiamo adattarci al cambiamento - Bellanca, Nicolò (Studi e saggi, 2020)
This Chapter examines the paths along which we humans could create an economy within planetary boundaries. To prevent the contraction of human activities from translating into a traumatic collapse, we should accept that contraction and indeed accelerate it. The negative impact on us would be greater, in fact, if we tried to stave off the decline, or slow it down. Given this paradox, the Chapter discusses how to support the return of socio-economic metabolism to the borders. In particular, it examines interventions at the individual, national and supranational level; mercantile policies; forms of collective and mutual action; measures that leverage systemic turning points. Finally, it thinks about how the relationship between humans and the environment is changing in terms of mutual "resonance".